2023
DOI: 10.3393/ac.2021.00983.0140
|View full text |Cite
|
Sign up to set email alerts
|

Intracorporeal versus extracorporeal anastomosis in laparoscopic right hemicolectomy: a retrospective cohort study of anastomotic complications

Abstract: Purpose: Laparoscopic right hemicolectomy (LRH) can be performed with an intracorporeal anastomosis (IA) or extracorporeal anastomosis (EA). It is not clear which technique is best. This study evaluated the impact of each anastomosis technique on perioperative safety and postoperative evolution.Methods: We performed a retrospective study at a tertiary colorectal surgery center. All patients who had an elective LRH from 2015 to 2019 were analyzed according to the anastomosis technique used.Results: In total, 28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
(48 reference statements)
1
8
0
Order By: Relevance
“…This can be explained by more mesocolon tissue being removed during this procedure, as attested by the greater length of resected intestines in ICA. Other studies found no statistically significant difference in lymph node harvest between the two groups 11 , 34 , 39 . However, these studies, including the current study, were all retrospective studies with limited sample sizes.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…This can be explained by more mesocolon tissue being removed during this procedure, as attested by the greater length of resected intestines in ICA. Other studies found no statistically significant difference in lymph node harvest between the two groups 11 , 34 , 39 . However, these studies, including the current study, were all retrospective studies with limited sample sizes.…”
Section: Discussionmentioning
confidence: 79%
“…In patients who underwent laparoscopic right hemicolectomy with ICA, a longer minimum margin was reported by previous studies (7 versus 5 cm, P = 0.026 11 ; 7.51 versus 5.40 cm, P = 0.010 13 ). Two studies 12 , 34 revealed that ICA mainly influenced the distal margin in laparoscopic right hemicolectomy. Similar to these results, ICA resulted in a longer distal margin compared with ECA in patients undergoing ERHC.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, historically, Ricci et al [ 16 ] and Wu et al [ 4 ] showed no significant difference in time to first flatus between ICA and ECA subgroups. Frigault et al [ 17 ] found no significant difference in time to the first bowel movement and reported a prolonged time to flatus for ICA participants. These contradictory results can be attributed to the challenges of early technique adoption, such as the steep learning curve due to the complexity of the ICA and the relatively longer operative duration.…”
Section: Discussionmentioning
confidence: 99%
“…An RCT of 140 patients comparing laparoscopic IA and EA found that the gastrointestinal function recovered earlier in patients with an IA (median, 2.3 days vs. 3.3 days; p = 0.003) and the incidence of ileus was lower (13% vs. 30%, p = 0.022) [13]. In contrast, Frigault et al [19] reported that the median time to the first f latus was longer in the IA group (p = 0.049), with a trend toward more ileus (17.2% vs. 9.0%, p = 0.07). This is probably because the definition of ileus is different in each study, and ileus is associated with a number of factors, and one of the most important factors is prior abdominal surgery.…”
Section: Postoperative Outcomesmentioning
confidence: 97%
“…The authors hypothesized that this phenomenon may be related to clear visualization of mesentery during the procedure, refinements of laparoscopic techniques and wide application of efficient laparoscopic instruments for effective hemostasis. However, several studies have reported no difference between the two groups regarding intraoperative blood loss [ 12 , 19 ].…”
Section: Operative Outcomesmentioning
confidence: 99%